Need Analysis of Designing an ESP Course for Sharia and Law Faculty Lecturers: A Case Study of Sayed Jamaluddin Afghani University, Afghanistan - Hazrat Usman Mashwani; Siti Maftuhah Damio; Nur Amalina Mohd Sharif (IJECA (International Journal of Education and Curriculum Application), 2024)
Learning English language is the need of the day. Being an international language and the language of modern education; English language learning has got special attention these days. The wide use of English language in various settings has increased the demand of its learning and has motivated everyone, regardless of their walk of life to learn English. To meet the demands of English-based education, especially in academic settings, there is a recognized need for English language learning. This study is a needs analysis of designing an ESP course for the lecturers of Sharia and Law faculty at Sayed Jamaluddin Afghani University (SJAU), Kunar, Afghanistan to improve their English language skills and take benefit of it in the academic setting. To be specific, lecturers’ perceptions towards the need of ESP course, choice of contents, level of difficulty and language skills that need improvement and inclusion in the ESP course were investigated. From 19 lecturers at the Faculty of Sharia and Law 10 lecturers were randomly selected as the sample of the study. An explorative mixed method case study design was used for the study. Mixed method design was used for the study to fully explore the research area and confirm the findings of qualitative data with the quantitative data. Semi-structured interviews containing 8 questions and a close ended questionnaire containing 16questions were used as the data collection instruments. The qualitative data was first thematically analyzed followed by quantitative data which was descriptively analyzed using frequencies and percentages through SPSS. The findings of the study revealed that the lecturers of Sharia and Law Faculty have positive perceptions towards the need of designing an ESP course for them. The proposed ESP course should use an intermediate level of contents and should focus on developing the four language skills especially reading and writing. Furthermore, the findings of the study revealed that the proposed ESP course should cover the grammar section to help the lecturers in developing their English grammar skills.